Soluble Transferrin Receptor and Soluble Transferrin Receptor/Log Ferritin Ratio are Correlated with Iron Status in Regular Hemodialysis Patients - Yenny Kandarini; Gede Wira Mahadita; Sianny Herawati; Anak Agung Wiradewi Lestari; Ketut Suega; I Gde Raka Widiana (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Monitoring of iron status in chronic kidney disease patients is important, however inflammation may hinder its monitoring. Soluble transferrin receptor (sTfR) is an alternative parameter to overcome this issue, whereas ferritin play a part in the inflammation process. Hence, the correlation between the sTfR ratio and the sTfR/log ferritin ratio with conventional iron status parameters in regular hemodialysis patients is necessary to be evaluated.METHODS: A cross-sectional was conducted in the current study. As many as 5 mL of blood (2 mL for sTfR and 3 mL for serum iron and ferritin levels) was collected. sTfR level was the blood-soluble transferrin receptor level measured by the enzyme-linked immunosorbent assay (ELISA). The amount of ferritin and serum iron was determined using the immunochemiluminescent process. To evaluate the correlation, the Pearson correlation test was used.RESULTS: A total of 80 subjects was included in this study. The mean of hemoglobin was 10.25±1.66 g/dL, serum iron was 58.19±26.56 g/dL, and the median ferritin was 520.4 (49.9-3606) ng/mL. The sTfR was significantly associated only with serum iron levels with a correlation coefficient of r=-0.242; p=0.031. The sTfR/log ferritin was significantly associated with serum iron l evels (InSI)(r=-0.255, p=0.022); and transferrin saturation (r=-0.295; p=0.008).CONCLUSION: sTfR/log ferritin has a negative and significant correlation with serum iron levels and transferrin saturation, while sTfR negatively correlated with serum iron levels. sTfR and sTfR/log ferritin may be considered as an alternative iron marker in inflammation setting such as CKD.KEYWORDS: sTfR/log ferritin, iron status, serum iron, ferritin, chronic kidney disease, hemodialysis